Method development for determination and removal of the selected steroids from water sources in selected areas around the Vaal River in South Africa using High performance Liquid Chromatography, Macadamia Activated Carbon and Solid Phase Extraction - Khotha, Doctor Elias (My University, 2018)
A simple and rapid method for determination of estrone (E1) and β-estradiol (E2) was developed and validated using high performance liquid chromatography (HPLC). The solutions of standards and sample were prepared with distilled water. HPLC separation was performed in isocratic method 50/50 (water/methanol) using 4.6 mm x 250 mm id film thickness 5 µm) XDB-C18 capillary column, detector DAD, UV on 254 nm, temperature 20 ºC with flow rate of 2 mL/min, sample volume 20 µL and run time of 10 min. Calibration curves were linear between concentration range 1.0 - 15.0 ppm. The method was validated for limit of detection and quantification, linearity, precision, trueness and specificity. Also the method was applied to directly and easily to the analysis of the E1 and E2. Adsorption experiments were carried out in batch mode using multistirrer in a series of Erlenmeyer ﬂasks of 50 ml capacity covered to prevent contamination having concentration ranges of E1 and E2 from 1 to 10 mg/L with adsorbent dose range 0.01 to 1 g at pH range 1 to 10 and temperature range 15°C to 35°C, placed on multistirrer. The results of the batch studies showed that simultaneous adsorption shows the maximum percent (91%) removal of E1 and (86 %) E2 at optimum temperature 25 °C of adsorbent dose 0.1 g, and pH 7. The mechanism, isotherms and kinetics of removal of two endocrine disrupting chemicals, estrone (E1) and β-estradiol (E2) by activated carbon adsorption were investigated in an agitated non-flow batch adsorption studies. Mathematical models were used to describe the adsorption phenomenon with the kinetic and thermodynamic parameters evaluated using the adsorption equilibrium data at varying temperatures. Higher adsorption rates were achieved at acidic to neutral pH ranges, with the sorption kinetic data showing a good fit to the pseudo second order rate equation and the Langmuir adsorption isotherm model for both E1 and E2. The Gibbs free energy were –16.68 kJ/mol and –17.34 kJ/mol for E1 and E2 respectively. The values of enthalpy for both E1 (84.50 kJ/mol) and E2 (90 kJ/mol) indicated a chemical nature of the sorption process. Both the isotherm and thermodynamic data obtained all supported the mechanism of adsorption of E1 and E2 to be mainly chemisorption’s supported by some physical attractions.
M. Tech (Department of Chemistry, Faculty of Applied and Computer Sciences) Vaal University of Technology.
Keywords: Estrone (E1), high performance liquid chromatography (HPLC), isotherms, adsorption; High performance liquid chromatography.; Carbon, Activated.; Steroids -- South Africa.